Pembelajaran Toleransi dalam Buku Ajar Pendidikan Agama Islam dan Budi Pekerti Jenjang Sekolah Menengah Pertama - Mawadda, Mita; Supriadi, Udin; Anwar, Saepul (Asosiasi Mahasiswa Program Pascasarjana | Universitas Islam Darussalam (UID) | Islamic University of Darussalam | Ciamis | Jawa Barat, 2023)
This study describes materials that contain tolerance learning in Islamic Religious Education and Moral Education textbooks at the junior high school level. The purpose of this study in general is to describe tolerance learning in Islamic Religious Education and Moral Education textbooks at the junior high school level. This research is important to do so that in the future tolerance learning materials can be delivered in accordance with the portion to students, so as to counteract intolerance and radicalism behavior for students. This study uses a literature study with a qualitative approach that analyzes the contents of textbooks on PAI and Budi Pekerti published by the Ministry of Education and Culture of the Merdeka Curriculum (Class 7 and 8 Books) and the Revised 2013 Curriculum (Class 9 Books). The data obtained was then collected and analyzed using the content analysis method. Data analysis techniques in this study used 3 data analysis steps, namely: data reduction, data display, and data verification. The results of the study show that textbooks for PAI & BP at the junior high school level promote tolerance. Thus, this research can be a reference for future researchers in researching tolerance learning related to other PAI books, as well as in the context of comparative textbooks.